CGIAR Seed Equal Initiative highlights women and smallholder farmers’ inclusion in seed information and delivery - Kujur, Aparajita; Puskur, Ranjitha; Escarez, Veronica Mae (International Rice Research Institute, 2024)
09-10 January 2024 (HYDERABAD, India) – The International Rice Research Institute (IRRI) organized a gender-responsive seed information and delivery pathways workshop on 9 and 10 January 2024 in Hyderabad. The activity was a part of the Work Package 6 of the CGIAR Seed Equal Initiative which focuses on increasing women's and marginalized farmers' access to seeds of improved, climate-resilient, and market-preferred varieties to improve their agricultural productivity and nutritional security.